IMPROVING STUDENTS’ WRITING SKILL THROUGH PERSONAL PHOTOGRAPH AT THE SECOND GRADE OF SMPN 35 MAKASSAR - Abdul Rahim Bin Mustapa; Andi Hamzah Fansury; Nurfaizah Sahib (Teaching English as a Foreign Language Overseas Journal, 2023)
The objective of the research was to find out wheter using personal photograph method was able to improve students’ writing skill at second grade of SMP Negeri Makassar. This Research was used experiment method and research subjects are students of SMP Negeri 35 Makassar Class VII (1). This Research takes students of class VIII (1) totaling 30 Students. In this research was conducted pre-test, treatment, and post-test. Data obtained through the provision of pre-test and post-test. the result showed differences in the average value of the each test. The average value of students in pre-test 65.56 and post-test was 93.30. This shows that the personal photograph method the positive effect on students’ writing skills class VIII (1) SMP Negeri 35 Makassar.